2002
DOI: 10.1086/340936
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray–emitting Young Stars in the Orion Nebula

Abstract: The Orion Nebula Cluster and the molecular cloud in its vicinity have been observed with the ACIS-I detector on board the Chandra X-ray Observatory with 23 hours exposure in two observations. We detect 1075 X-ray sources, most with sub-arcsecond positional accuracy. Ninety-one percent of the sources are spatially associated with known stellar members of the cluster, and an additional 7% are newly identified deeply embedded cloud members. This provides the largest Xray study of a pre-main sequence stellar popul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
416
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 278 publications
(463 citation statements)
references
References 99 publications
(153 reference statements)
39
416
8
Order By: Relevance
“…The resulting spectrum, shown in Figure 2, is unusually soft, with peak emission at 0.7 keV and no photons above 1.5 keV. Bestfit parameters with 90% confidence levels are temperature keV, line-of-sight column density L Ӎ 1 # 10 X powerful solar flare, the typical temperatures rise to T Ӎ 1-2 keV, much hotter than seen in TWA 5B but typical of other PMS stars and BDs (e.g., Feigelson et al 2002). A light curve of the photon arrival times was examined and no significant variations were found during the 11 ks duration of the observation.…”
Section: Observations and Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The resulting spectrum, shown in Figure 2, is unusually soft, with peak emission at 0.7 keV and no photons above 1.5 keV. Bestfit parameters with 90% confidence levels are temperature keV, line-of-sight column density L Ӎ 1 # 10 X powerful solar flare, the typical temperatures rise to T Ӎ 1-2 keV, much hotter than seen in TWA 5B but typical of other PMS stars and BDs (e.g., Feigelson et al 2002). A light curve of the photon arrival times was examined and no significant variations were found during the 11 ks duration of the observation.…”
Section: Observations and Resultsmentioning
confidence: 93%
“…However, X-rays from several young BDs with ages Myr t ∼ 1 old were discovered with ROSAT in nearby star-forming regions (Neuhäuser & Comerón 1998;Neuhäuser et al 1999;Mokler & Stelzer 2002). After the launch of the Chandra X-Ray Observatory, the number of X-ray-detected young BDs has increased an order of magnitude Imanishi, Koyama, & Tsuboi 2001a;Imanishi, Tsujimoto, & Koyama 2001b;Preibisch & Zinnecker 2001;Feigelson et al 2002). In young stellar clusters around 1 Myr old, hard and variable Xrays are now detected from about one-fourth of the BD population near the "saturation level" of .…”
Section: Introductionmentioning
confidence: 99%
“…This problem of small and often biased samples has, however, recently been overcome with two Chandra studies of the Orion Nebula Cluster (ONC) (Feigelson et al 2002a;Flaccomio et al 2003b), both of which found no significant relation between X-ray activity and rotation. This strongly puts into question the solar-like dynamo activity scenario for TTSs.…”
Section: Open Questions About the X-ray Activity From Ttssmentioning
confidence: 99%
“…The ONC has been observed with both imaging instruments on board Chandra. The results of two Advanced CCD Imaging Spectrometer observations with a combined exposure time of 23 hr were reported in Garmire et al (2000) and Feigelson et al (2002aFeigelson et al ( , 2002bFeigelson et al ( , 2003. A total of 1075 individual sources were detected, 91% of which could be identified with known stellar members of the cluster.…”
Section: Properties Of the Onc And Previous X-ray Observationsmentioning
confidence: 99%
“…In particular, following up on pioneering ROSAT observations, intermediate to distant clouds have been covered by Chandra: the Orion nebula (Garmire et al 2000;Feigelson et al 2002Feigelson et al , 2003Flaccomio et al 2003), part of the Rosette nebula and molecular cloud, together with M17 (Townsley et al 2003;Wang et al 2008Wang et al , 2009); Mon R2 (Kohno et al 2002); RCW38 (Wolk et al 2002); M16 (Linsky et al 2007), and by XMMNewton: M8 (Rauw et al 2002); Carina (Albacete Colombo et al 2003); Vela OB2 (Jeffries et al 2009); Orion (López-Santiago & Caballero 2008); and others. Up to thousands of point X-ray sources per cloud are detected, almost all identified with young stars, down to the brown dwarf regime.…”
Section: Search For Young Stars Based On X-ray Datamentioning
confidence: 99%